The demographic transition: Causes and consequences - Oded Galor (Institute for the Study of Labor (IZA), 2012)
This paper develops the theoretical foundations and the testable implications of the various mechanisms that have been proposed as possible triggers for the demographic transition. Moreover, it examines the empirical validity of each of the theories and their significance for the understanding of the transition from stagnation to growth. The analysis suggests that the rise in the demand for human capital in the process of development was the main trigger for the decline in fertility and the transition to modern growth.
urn:nbn:de:101:1-201205025990
Keywords: O10; J1; 330; demographic transition; gender gap; human capital; fertility; mortality; Unified Growth Theory; Demographischer Übergang; Bevölkerungsentwicklung; Wirtschaftswachstum; Humankapital; Geburtenrate; Sterblichkeit; Theorie; Welt